IMPLEMENTASI SOSIALISASI TENTANG MIGRASI SIARAN TELEVISI ANALOG KE DIGITAL DAN PENDAMPINGAN PEMBAGIAN SET TOP BOX (STB) KEPADA MASYARAKAT TIDAK MAMPU - April Laksana; Achmad Nashrudin; Riska Ferdiana (LPPM Universitas Bina Bangsa, 2022)
Television broadcasts (TV) are a very powerful medium (a powerful medium) in disseminating information to the public simultaneously, TV broadcasts also have a broad reach and are able to eliminate geographical boundaries, political systems and community culture. Broadcasting digitization is a technological dynamic that is a necessity to be implemented. Digital television broadcasting in Indonesia is unavoidable and the development of technology. The broadcasting digitization policy is set by the government by considering the future benefits of implementing digital technology in the broadcasting sector. The government and the KPID Province Bhave jointly drafted regulations that can accommodate the aspirations of media activists and the public so that broadcast migration from analog to digital can be carried out immediately. The purpose of the Indonesian Broadcasting Commission for the Banten Province and providers of national television stations or MUX such as Trans TV, SCTV, RCTI, INDOSIAR and others in the supervision of distribution and implementation of socialization that is promoted for the transfer of analog TV broadcasts to digital, as a framework for developing digital TV technology. by using the Set Top Box device